2021
DOI: 10.1111/mmi.14845
|View full text |Cite
|
Sign up to set email alerts
|

The 3′UTR‐derived sRNA RsaG coordinates redox homeostasis and metabolism adaptation in response to glucose‐6‐phosphate uptake in Staphylococcus aureus

Abstract: Staphylococcus aureus is usually described as an extracellular opportunistic pathogen, infecting a wide range of organs and tissues.However, it also invades and replicates in various phagocytic or nonphagocytic host cells (Hamza & Li, 2014). To be successful as a pathogen, this bacterium needs to adapt to the hostile environment of the host and must acquire imposed nutriments for its survival.Consequently, the staphylococcal genome encodes several transporters for metabolites (sugars, metals, amino acids, etc.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 66 publications
1
30
0
Order By: Relevance
“…RsaC was found to repress the expression of the superoxide dismutase SodA, which is involved in the oxidative-stress response [40]. A recent study of the RsaG targetome revealed mRNAs of the transcription factors Rex, CcpA, and SarA as molecular targets [42]. Interestingly, studies conducted on both RsaI and RsaG showed that these two sRNAs interact together, which suggests complex sRNA regulatory networks (see Section 6 of this review).…”
Section: Experimental Approachesmentioning
confidence: 97%
See 4 more Smart Citations
“…RsaC was found to repress the expression of the superoxide dismutase SodA, which is involved in the oxidative-stress response [40]. A recent study of the RsaG targetome revealed mRNAs of the transcription factors Rex, CcpA, and SarA as molecular targets [42]. Interestingly, studies conducted on both RsaI and RsaG showed that these two sRNAs interact together, which suggests complex sRNA regulatory networks (see Section 6 of this review).…”
Section: Experimental Approachesmentioning
confidence: 97%
“…The authors identified mRNAs encoding transcription factor MgrA, the SsaA protein involved in peptidoglycan synthesis, and the anti-inflammatory protein FLIPr, as the primary targets. A similar approach was used to identify the targetomes of RsaI, RsaC, SprY, and RsaG [39][40][41][42]. The use of RsaI as a bait allowed for the identification of mRNAs encoding a permease for glucose uptake (GlcU_2), along with Fn3K and IcaR, which are involved in protection against high concentrations of glucose and the repression of exopolysaccharide production, respectively [39].…”
Section: Experimental Approachesmentioning
confidence: 99%
See 3 more Smart Citations